Effects of mechanical ventilation on neurodevelopment at 12 months in preterm low birth weight pediatric patients: a systematic review - Vargas Caicedo, Valerie; de la Plaza San Frutos, Marta; Sosa Reina, Maria Dolores; Garcia Arrabe, Maria; Salniccia, Federico; Reina Aguilar, Clara; Estrada Barranco, Cecilia (Frontiers in Pediatrics, 2024)
The objective of this review is to know the existing scientific evidence about the effects of mechanical ventilation (MV) on neurological development in low-birth-weight premature pediatric patients after 12 months of life, taking as background the direct impact that ventilation has on the central nervous system in the newborn during the first days of life. Methods: A systematic search was carried out between 2003 and 2024 in the data bases of: PUBMED, Cochrane Library Plus, PEDro, CINAHL, and SciELO, and two investigators scored the articles according to the Newcastle-Ottawa Assessment scale. Results: Were found 129 non-replicated articles, and 10 cohort and cross-sectional studies were selected that performed an assessment of neurodevelopment in the three spheres after 12 months of life in corrected age of premature infants exposed to ventilator support and related the two variables independently. Conclusions: Mechanical ventilation is an independent neurodevelopmental risk factor in low-birth-weight preterm infants. The time of exposure and the type of ventilation were the variables with the most scientific evidence.